2021
DOI: 10.1128/aem.02662-20
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal Enterotoxin Gene Cluster: Prediction of Enterotoxin (SEG and SEI) Production and of the Source of Food Poisoning on the Basis of v Saβ Typing

Abstract: Currently only five (SEA-SEE) out of 27 known staphylococcal enterotoxins can be analyzed using commercially available kits.Six genes (seg, sei, sem, sen, seo, and seu), encoding putative and undetectable enterotoxins, are located on the enterotoxin gene cluster (egc) which is part of the Staphylococcus aureus genomic island vSaβ. These enterotoxins have been described as likely being involved in staphylococcal food poisoning outbreaks.The aim of the present study was to determine if whole genome data can be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 77 publications
2
18
0
Order By: Relevance
“…Different studies have found that S. aureus CC30 is predominant among human nasal carriers of the bacterium [33], and in cases of bacteremia in Denmark [30]. Although it has also been isolated from RTE food [4], it is not one of the major clonal complexes of porcine origin. We cannot rule out a human origin of those isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have found that S. aureus CC30 is predominant among human nasal carriers of the bacterium [33], and in cases of bacteremia in Denmark [30]. Although it has also been isolated from RTE food [4], it is not one of the major clonal complexes of porcine origin. We cannot rule out a human origin of those isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcal enterotoxins are the main virulence factors associated with S. aureus and the primary cause of staphylococcal food poisoning. Most of the staphylococcal food poisoning outbreaks are classified as weak-evidence outbreaks, as only the classical enterotoxins SEA, SEB, SEC, SED and SEE can be detected commercially [4]. Together with these five SEs, new described enterotoxins and staphylococcal enterotoxin-like proteins Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, their expression varies among different strains of S. aureus . Nevertheless, the enterotoxin gene cluster (EGC) involves six SAgs (SEG, SElI, SElM, SElN, SElO, SElU) that occur in a set particularly often [ 11 ]. Furthermore, selected novel SEls were identified as core genome elements [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, publicly available reference databases for virulence gene detection in S. aureus isolates (Joensen et al, 2014;Liu et al, 2019;Sayers et al, 2019;Merda et al, 2020) do not enable complete se gene profiling (e.g., ses, set, selw to selz, sel26 and sel27 are missing in the VFDB_Full database, and ses, set, selv to selz, sel26 and sel27 in the VirulenceFinder DataBase) or subtyping of se variants (because they are not or ambiguously annotated in the databases). Studies using these databases as such (Huang et al, 2017;Petit and Read, 2018;Fursova et al, 2020;Karki et al, 2020;Merda et al, 2020;Schwendimann et al, 2021), thus risk underestimating the prevalence of se genes, potentially affecting obtained results. Indeed, more se genes were reported to be present in the isolates with publicly available WGS data after reanalysis with our methods compared with their previously WGS-determined se gene profiles, mainly because of the lack of complete databases in the other studies (Fursova et al, 2020;Merda et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to its unparalleled resolution standing out compared with conventional methods (Anderson et al, 2014;Moore et al, 2015;Cunningham et al, 2017;Cremers et al, 2020), it has moreover become the ultimate tool for inferring phylogenetic relationships between bacterial isolates, using core genome MLST (cgMLST) or single nucleotide polymorphism (SNP) analysis. Although WGS was already used to analyze Methicillin-resistant S. aureus strains responsible for nosocomial infections (Anderson et al, 2014;Moore et al, 2015;Peacock and Paterson, 2015;Cunningham et al, 2017;Sabat et al, 2017), it has been scarcely applied for SFP investigation despite the advantages highlighted above (Merda et al, 2020;Schwendimann et al, 2021).…”
Section: Introductionmentioning
confidence: 99%